Haasil - Shergill, Jimmy 1970-; Bhatt, Hrishitaa; Khan, Irrfan 1962-2020; Anand, Tinnu; Pandey, Sudhir; Saxena, Sharat; Zutshi, Rajendranath 1961-; Yadav, Rajpal 1973-; Ali, Murad; Sinhan, Aseem (Shemaroo Video, 2006)
Anirudh and Niharika, college students, fall in love but Anirudh is soon caught up in college politics dominated by two rivals. After Anirudh witnesses one of them commit murder, he is drawn deeper into political intrigue, gangs, and crime, threatening his relationship with Niharika